(untitled) (Revista Latino-Americana de Enfermagem, 2002)
This descriptive and exploratory study aimed at apprehending, by means of interviews, the experiences of children and adolescents with a chronic disease as it is felt by them. The results showed that the lives of children and adolescents are changed by frequent hospitalizations and by the limitations imposed by the disease, which causes alterations particularly in their schooling process. Considering that children and adolescents experience complex feelings and situations in the everyday routine of living with a chronic disease, it is important that health care professionals learn about such needs and incorporate them to care planning, aiming at providing effective intervention in order to promote growth and development.